Membangun Kemampuan Komunikasi Matematis Siswa Melalui Lesson Study: Sebuah Perspektif - Didi Suhaedi; Erwin Harahap (Matematika, 2018)
Abstrak. Komunikasi matematis, sebagai bagian dari daya matematis, merupakan suatu kemampuan yang mesti dipelajari dan dikuasai oleh siswa dalam mempelajari materi-materi Matematika. Tumbuh kembangnya komunikasi matematis siswa sangat dipengaruhi oleh partisipasi aktif siswa secara kolaboratif dalam proses pembelajaran Matematika. Lesson study sebagai pembelajaran yang berorientasi pada siswa (student center) memberikan ruang yang cukup bagi siswa untuk mengembangkan kemampuan komunikasi matematisnya. Diskusi kelompok dan kelas dapat menjadi wahana bagi siswa untuk melakukan peer colaboration dalam mengembangkan kemampuan komunikasi matematis siswa dan menguasai materi Matematika. Artikel ini mendiskusikan tentang konstruksi kemampuan komunikasi matematis siswa melalui lesson study.Kata kunci: komunikasi matematis, lesson study Building Student’s Mathematical Communication Ability Through Lesson Study: A PerspectiveAbstract. Mathematical communication, as part of mathematical power, is an ability that must be learned and mastered by students in learning Mathematics materials. The growth of mathematical communication of students is strongly influenced by the active participation of students collaboratively in the process of learning Mathematics. Lesson study as student-oriented learning (student center) provides sufficient space for students to develop mathematical communication ability. Group and class discussions can be a vehicle for students to do peer collaboration in developing students' mathematical communication ability and mastering Mathematical material. This article discusses the construction of students' mathematical communication ability through lesson study.Keywords: mathematical communication, lesson study